2011
DOI: 10.1002/app.33860
|View full text |Cite
|
Sign up to set email alerts
|

Determining the elastic properties of modified polystyrenes by sound velocity measurements

Abstract: The effect of the binding of various polyfunctional groups to polystyrene's (PS's) aromatic ring on the elastic properties of the PS were investigated by an ultrasonic method. Various sets of samples were prepared by chemical modification of pure PSs having different molecular weights with SA, maleic anhydride, and phthalic anhydride. The ultrasonic wave velocities of modified PSs were measured with the pulse-echo method at room temperature by a computercontrolled analyzer and a digital oscilloscope. The value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…It can be stated that different functional groups may affect mechanical properties of composites in different ways. To understand the effect of molecular structure, three various carboxylic (COOH) functional groups with aromatic, saturated aliphatic and unsaturated aliphatic parts in case of PhA, SA, and MA, respectively are specifically studied 60. As seen from Figure 1, when pure PS modified with SA, COCH 2 CH 2 COOH polyfunctional group was bound to aromatic ring of pure PS, when pure PS modified with MA, COCHCHCOOH polyfunctional group was bound to aromatic ring of pure PS and when pure PS modified with PhA, COC 6 H 4 COOH polyfunctional group was bound to aromatic ring of pure PS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be stated that different functional groups may affect mechanical properties of composites in different ways. To understand the effect of molecular structure, three various carboxylic (COOH) functional groups with aromatic, saturated aliphatic and unsaturated aliphatic parts in case of PhA, SA, and MA, respectively are specifically studied 60. As seen from Figure 1, when pure PS modified with SA, COCH 2 CH 2 COOH polyfunctional group was bound to aromatic ring of pure PS, when pure PS modified with MA, COCHCHCOOH polyfunctional group was bound to aromatic ring of pure PS and when pure PS modified with PhA, COC 6 H 4 COOH polyfunctional group was bound to aromatic ring of pure PS.…”
Section: Resultsmentioning
confidence: 99%
“…One of the important results of this study is that showed that the best way for improving the mechanical properties of pure PS is to producing CPSs. In fact the researches60, 85, 86 made before had shown that modifying PS with various organic anhydrides, increases the elasticity properties of PS. But modifying PS by various anhydrides is an expensive way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Included amongst these are medical imaging, dentistry, particle sizing, food processing, welding, waste water treatment, and surgical processes 25. Furthermore, ultrasonic methods have been successfully used to monitor polymer processing,26 chemical reactions,27, 28 film formation from aqueous polymer dispersions,29 glue processes, crystallization in polymers,30, 31 and also characterization of polymers 32. Thus, recently, a lot of attempts have been made to study the sound velocity and attenuation of polymers 33–42.…”
Section: Introductionmentioning
confidence: 99%
“…There are weak electrostatic gravitational forces (e.g., van der Waals forces, hydrogen bonds) between the molecular chains. These van der Waals forces and hydrogen bonds keep the chains of molecules close to each other 32, 45. The longitudinal modulus is related with bonds which creates the polymer chains between monomers.…”
Section: Introductionmentioning
confidence: 99%